1997
DOI: 10.1002/(sici)1520-6300(1997)9:1<63::aid-ajhb9>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of multiple frequency bioelectrical impedance analysis: An intermachine comparison

Abstract: The technical reliability (i.e., interinstrument and interoperator reliability) of three SEAC‐swept frequency bioimpedance monitors was assessed for both errors of measurement and associated analyses. In addition, intraoperator and intrainstrument variability was evaluated for repeat measures over a 4‐hour period. The measured impedance values from a range of resistance‐capacitance circuits were accurate to within 3% of theoretical values over a range of 50–800 ohms. Similarly, phase was measured over the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 27 publications
3
22
1
Order By: Relevance
“…when used to calculate R i . 11 The mean value for the inter-leg ratio of R 0 (dominant:nondominant) in females was very close to unity, 0.999 (AE0.056), while in males the value was slightly further from unity, 0.994 (AE0.050), reflecting the slight asymmetry seen in R 0 values. The impedance ratios were not significantly correlated with either BMI (r ¼ 0.054 and r ¼ 0.109 for females and males, respectively) or the age (r ¼ 0.117 and r ¼ 0.013 for females and males, respectively) of participants.…”
Section: Resultsmentioning
confidence: 99%
“…when used to calculate R i . 11 The mean value for the inter-leg ratio of R 0 (dominant:nondominant) in females was very close to unity, 0.999 (AE0.056), while in males the value was slightly further from unity, 0.994 (AE0.050), reflecting the slight asymmetry seen in R 0 values. The impedance ratios were not significantly correlated with either BMI (r ¼ 0.054 and r ¼ 0.109 for females and males, respectively) or the age (r ¼ 0.117 and r ¼ 0.013 for females and males, respectively) of participants.…”
Section: Resultsmentioning
confidence: 99%
“…values between the SFB3 and SFB7 instruments have been determined when both are tested on participants or electronic test circuits. 9 Therefore, all SFB3 data were converted to equivalent SFB7 data using the conversion factors provided by Ward. 10 Data processing and analysis Data from both instruments were analyzed according to Cole theory, 11 using the manufacturer's software (Bioimp version 4.8.0.0, Impedimed Ltd.), to provide values for R 0 and R ?.…”
Section: Measurement Of Limb Impedancementioning
confidence: 87%
“…Generally, the default program settings were used for analyses; however, for some data sets, the analysis was optimized by adjustment of the frequency ''window'' used for fitting the data to the Cole model guided by minimizing the standard error of the estimate (SEE) for the curve fitting procedure. 9 The SEE for all analyses was <1%.…”
Section: Measurement Of Limb Impedancementioning
confidence: 99%
“…This indicates that such a 20% change in skin water would be essentially undetectable with multi-frequency BIS analyzers that have a reported accuracy of -3% for resistance R 0. 65 Using the same model it can be shown that for an increase of 20% in skin tissue water the arm volume changes less than 2% (i.e., such a 20% change in skin water volume is practically undetectable by arm volume measurement). Calculations based on this simple, but representative model, suggests that the main route of electric current in the BIS technique is through the well-conducting (subfascial) muscle component that is largely spared of swelling and to a lesser amount through the skin where early lymphedema is thought to manifest.…”
Section: Origin Of Physiological Information Between the Tdc And Bis mentioning
confidence: 99%